Evaluasi Kurikululum Terpadu dalam Mengembangkan Karakter Peserta Didik - S. Sudayat; Ishak Abdulhak (Inovasi Kurikulum, 2015)
Background ofthis study is that social problems of increasingly widespread phenomenon ofmoral decline among learners, especially in primary schools in West Java province, for example: the habit ofcheating, skipping school, pemalakkan, brawl, and smoke due to the practice ofeducation in schools is not integrated in the deveiopment of the human person as a whole . This study aims to assess the integrated curriculum SDIT in developing the character of learners in the province of West Java dimensional views of the philosophy of education, community support, curriculurn documents, the learning process and learning outcomes as a unified whole and integrated. This study uses a model evaluation CIPP (Context, Input, Process, and Product) by using purposive randorn sampling and analysis techniques combined (rnixed methods). The results of the analysis indicate that: First: the cornerstone of the philosophy of an integrated curriculum that is used SDIT has the right to develop the character of learners in the province of West Java, Second: the integrated curriculum documents used SDIT effective in developing the character of learners in the province of West Java, Third: integrated curriculum leaming process SDIT effective in developing the character of learners in West Java, Fourth: support means infrastructures in an integrated curriculum SDIT used effectively to develop the character of learners in the province of West Java. Fifth, the results ofan integrated curriculum that is used SDIT have developed the character of learners in West Java. Recommendations research in the form of context, input, process and results are given to Policy Makers, School Principal, Electric Education, Parents of Students and Further research.